Improving the Comprehension Skills of Grade 6 Pupils at Tuhian Elementary School through Catch-Up Fridays - Talain, Allan; Cruzado, Jonny (International Journal of Theory and Application in Elementary and Secondary School Education, 2024)
True experimental research design was utilized in this study. Specifically, pretest posttest control group design was employed to demonstrate causality between the intervention and an outcome. The respondents involved 28 Grade 6 learners who comprised the control and experimental groups, which were formed through simple random sampling. In connection, the reading performance of the respondents in both groups was assessed using the standardized passages from Phil-IRI. The data gathered were analyzed and interpreted using Weighted Mean. In connection, a test of normality of data was conducted using Kolmogorov-Smirnov Test. The results provide good evidence that the data are normally distributed. Thus, independent t-test, as a parametric test, was utilized to statistically treat the data. Meanwhile, Lavene’s test for equality of variance was employed to test the variances of pre-test scores both in control and experimental groups. The results suggest that there is no difference between the variances of both groups, which means that there is homogeneity before the implementation of Catch-up Fridays in the treatment group and teacher-led reading approach in the control group. The study revealed that there was no significant difference between the pre-test scores of the control and experimental groups in terms of comprehension, which indicated that there was homogeneity before implementing Catch-up Fridays. On the other hand, after the treatment, there was a significant difference between the post-test scores of the two groups. Therefore, there was a marked improvement in the comprehension performance of the respondents. This demonstrated that the respondents’ comprehension skills have improved. In this regard, this study revealed that Catch-up Fridays as a reading intervention program be adopted by other schools to enhance struggling learners’ comprehension skills.